SLC30A10: A novel manganese transporter - Chen, Pan (Worm, 2015)
Homozygous mutations in SLC30A10 cause familial parkinsonism associated with manganese (Mn) retention. We recently identified SLC30A10 to be a cell surface-localized Mn efflux transporter and demonstrated that parkinsonism-causing mutations block its intracellular trafficking and efflux function. In C. elegans, SLC30A10 over-expression protected against Mn-induced lethality and dopaminergic neurotoxicity, consistent with results in mammalian systems. Here, we present new data about SLC30A10 function in C. elegans. SLC30A10 expression did not protect worms against ZnSO(4)toxicity, suggesting that SLC30A10 does not mediate Zn export in C. elegans. Furthermore, while a blast search identified 5 potential SLC30A10 homologs in worms (cdf-1, cdf-2, ttm-1 and toc-1; sequence identity <35%), knock-down of these genes showed a tendency of increased survival after Mn exposure (although only ttm-1 was statistically significant), suggesting that the worm homologs may function differently.